Quality of sexual life and attitudes toward menopause among postmenopausal women living in northern cyprus: A cross-sectional study - Fatma Uslu-Sahan; Asli Er-Korucu; Arzu Abic (Wolters Kluwer Medknow Publications, 2023)
Background: Most middle-aged women in the menopausal period consider sexuality an important part of life. The aim of the present study was to investigate the factors affecting the quality of sexual life and attitudes toward menopause in postmenopausal women and the effects of their attitudes toward menopause on the quality of sexual life. Materials and Methods: This cross-sectional study was conducted with postmenopausal women in the Turkish Republic of Northern Cyprus between July 2021 and April 2022. The research sample consisted of 255 postmenopausal women. The Attitudes Toward Menopause Scale and the Sexual Quality of Life Scale (SQLS) were used to collect data. The questionnaire forms were administered online. The data were analyzed using the independent t-test, analysis of variance, Tukey's test, Pearson's correlation, and linear regression analysis. Results: The mean score of the participants on the SQLS was 43.54 ± 12.56 and the mean score of the Attitudes Toward Menopause Scale was 60.39 ± 16.29. The study revealed that variables such as age, level of education, employment status, duration of menopause, and knowledge about menopause have an effect on women's sexual life quality. In addition to the listed variables, income level was found to affect attitudes toward menopause. A positive attitude toward menopause causes an increase in the level of sexual life quality (β = 0.544, R2 = 0.30, F = 106.260, R = 0.544, P = 0.001). Conclusions: The attitudes of postmenopausal women toward menopause are an important determinant of their sexual life quality. For this reason, it is recommended to develop and implement training programs that can improve sexual health of women and their attitudes toward menopause.